Ultra-processed and highly palatable foods on the development of obesity - Vindas-Smith, Rebeca (2021)
Introduction: Obesity is a multifactorial trait provoked by the interaction of biological, environmental, psychosocial, and socioeconomic factors. Proposal: The goal of the present review is to discuss the role of ultra-processed and highly palatable foods (UPHP) in the development of the obesity epidemic through an exploratory-descriptive review and to present some suggestions for controlling its consumption. Arguments for discussion: UPHP are energy dense foods with high contents of fat and sugar. UPHP are formulated with many industrial additives used for enhancing flavor, shelf life, and the stability of their components. UPHP used to contain diverse chemicals known as endocrine disruptors (EDC), which are transferred from packaging to foods, with bisphenol A and phthalates as the most common EDC. The EDC disrupt different hormonal signaling pathways affecting the metabolism of the adipose tissue and other endocrine systems. The overconsumption of UPHP induces neuroplastic changes in the brain reward system that increases their consumption, leading to body fat accumulation. In addition, the overconsumption of UPHP alters the composition of the intestinal microbiome (dysbiosis), which is associated with the development of obesity. Conclusions: The overconsumption of UPHP increases the risk of obesity and its related chronic, non-communicable diseases, especially when consumption initiates during early life. To counteract this problem, we proposed the following actions: changing the structure of the market-food basket, incorporating regulations to reduce the UPHP supply in and around educational centers, creating new taxes upon UPHP, and strengthening the research regarding obesity, and the effects of UPHP and EDC.